Influence of seed concentration and storage time on the rheological, textural, and microscopic crystallization attributes of Apis mellifera honey - Ozmen, Duygu; Demircan, Huseyin; Yildirim, Rusen Metin; Waseem, Muhammad; Basdogan, Hakan; Toker, Omer Said; Osei Tutu, Crossby (ELSEVIER, 2025)
This study aimed to evaluate the impacts of seed honey supplementation at concentrations of 5, 10, and 15 % (w/w) and storage time (up to 12 days at 14 degrees C) on the rheological, textural, crystallization, and colour attributes of honey. The rheological properties, including the apparent viscosity, loss modulus, and storage modulus, were assessed using a rheometer. Textural properties, such as hardness and spreadability, were measured using a texture analyzer. The L* values were determined to assess the crystallization process, and microscopic imaging was used to observe the size and formation of the sugar crystals. Results showed that the apparent viscosity increased significantly (p < 0.05) from 13.1 Pa.s to 38.5 Pa.s (194 % up arrow) as both the seed concentration and storage time increased from 0 %-15 % and 0-12 days, respectively. The highest G value (2756 Pa) was observed on the 9th day for the 15 % seed concentration. The work of shear decreased with increasing seed concentrations but increased over storage time. L* values, an indicator of crystallization, showed a significant increase across concentrations and storage time. Microscopic examination of seed crystals anticipated zero crystals at 0-12th day in control; however, 6th and 12th days of storage at 10 % and 15 % addition of seeds increased size and magnitudes of crystals than 5 %. Conclusively, adding seed honey at levels up to 10 % and allowing 9 days of storage effectively promotes the shear-thinning behaviour desirable in spreadable honey products. Creamed honey offers improved texture and user convenience, enhancing product versatility without compromising flavour. These results provide a practical basis for optimizing processing conditions in commercial honey formulation to meet diverse consumer and market needs.
Keywords: Honey crystallization; Seed concentration; Storage time; Rheology; Texture; Gastronomy; BIOACTIVE PROPERTIES; BEHAVIOR; ORIGIN; Chemistry; Food Science & Technology